Sayings of Gorakhnath annotated translations from the Gorakh Bani - Gorakṣanātha Heiliger ca. 10. Jh.; Djurdjevic, Gordan; Siṃha, Śukadeva 1933-2007 (New York Oxford University Press, 2019)
Introduction -- Sayings of Gorakhnath. Sabads -- Pads -- The Overview of Teaching -- The String of Breaths -- The Royal Understanding -- Self-Understanding -- Measure of Fearlessness -- Yoga -- Fifteen Days -- Seven Days -- Machindra's Instruction to Gorakh -- A Line of Hair -- The Ornament of Wisdom -- The Five Measures -- Appendix: The Victory of Gorakha
Bibliografie Seite 217-223 und Index
Übersetzung aus dem Hindi
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Gorakhanātha -- Translations into English; Nātha sect -- Poetry